2018
DOI: 10.1063/1674-0068/31/cjcp1709173
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Solvent Effect on Mechanical Properties of Poly(ether ether ketone) Using Nano-indentation

Abstract: Poly(ether ether ketone) (PEEK) is a high-performance semi-crystalline thermoplastic polymer. Exposure of the polymeric surface to solvents can have a strong effect like softening/swelling of polymeric network or dissolution. In this study, nano-indentation analysis was performed to study the effect of acetone on the surface mechanical properties of PEEK using different exposure time. The experiments were performed with a constant loading rate (10 nm/s) to a maximum indentation displacement (1000 nm). A 30-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Interestingly, the blend sample 50% ABS/50% PC exhibited a significantly lower hardness value of 0.16 GPa compared to the values of 0.22 and 0.27 GPa for neat ABS and PC, respectively. This difference may have risen due to some surface effects during sample preparation or environmental effect [37]. Elastic modulus of all ABS/PC samples at different penetration depths has been presented in Figure 5.…”
Section: Nano-indentationmentioning
confidence: 99%
“…Interestingly, the blend sample 50% ABS/50% PC exhibited a significantly lower hardness value of 0.16 GPa compared to the values of 0.22 and 0.27 GPa for neat ABS and PC, respectively. This difference may have risen due to some surface effects during sample preparation or environmental effect [37]. Elastic modulus of all ABS/PC samples at different penetration depths has been presented in Figure 5.…”
Section: Nano-indentationmentioning
confidence: 99%
“…It was observed that semi-crystalline PEEK exhibited a significantly inert behavior to ordinary organic solvents but water and chlorinated organic solvents triggered deterioration in the surface mechanical properties. Recently, we reported the influence of acetone environment, as a function of different exposure times, on the nano-mechanical properties of PEEK using nanoindentation method (17). The results showed that the nano-mechanical properties of PEEK displayed a decreasing trend as a function of increasing exposure times to the acetone environment, which was linked with the swelling/softening of polymeric network.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the use of this solubility parameter has a long history and it is a manifestation of the relative solvency behavior of a liquid. Furthermore, these solvents were selected to see their effect on bulk properties, instead of nano-mechanical properties as reported earlier (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, knowledge of the surface properties are important considerations for material selection and design in applications involving surface engineering and tribological contacts. The mechanical properties of the outermost surface layers have been conveniently investigated using the nano-indentation technique for the past two decades by us and a number of other researchers [6][7][8][9][10][11][12][13][14][15][16][17][18]. Nano-indentation, a non-destructive technique, is a powerful tool for analyzing the surface mechanical properties of a wide variety of materials, including polymers, metals, composites, and biological entities.…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of these studies revealed that the addition of nanomaterials improved the modulus, hardness, and coefficient of friction of the prepared composites [31]. Recently, we described the effect of acetone exposure, in relation to different exposure times, on the surface properties of poly (ether ether ketone) (PEEK) using a nano-indentation technique [10]. The results showed a decreasing trend in the surface properties of PEEK as a function of exposure time to the acetone, which was attributed to the softening of the polymer network.…”
Section: Introductionmentioning
confidence: 99%